Assessment of service provider preparedness and concerns in the process of implementing the National Health Insurance Scheme in Ghana : a study of the Upper West Region - Basadi, Richard Angwaasuwe (Health Economics Unit, 2014)
Includes bibliographical references ( leaves 85-88).